Project-Based Learning Model for Fifth Grade Students: Testing Theme 2 Thematic Teaching Materials Validity - Betridamela Nasti; Nur Azmi Alwi (AL-ISHLAH: Jurnal Pendidikan, 2023)
Education will be better and more focused by following an increasingly sophisticated era. Environmental changes that are progressively developing also affect the development of education. The 2013 curriculum has a more complex level of material than before. Therefore, effectiveness in the teaching and learning process must be improved, one of which is in learning tools. Teaching materials are a set of learning activities that affect the effectiveness of delivering material to students. The purpose of this research is to produce tematic teaching materials theme 2 that are effective and efficient using the Project Based on the Learning model. Tematic teaching materials theme 2 are developed based on an analysis of students and teachers. The analysis uses the 4D model technique, which uses four stages. The four stages are definition, design, development, and dissemination. The data was obtained from the results of interviews and questionnaires. The preparation of teaching materials begins with observation and content validation by a team of experts. This research produces teaching materials based on the PJBL model with good validity.